X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lou; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging